Lunar elemental abundances as derived from Chandrayaan-2 - Narendranath S.; Pillai N.S.; Bhatt M.; Vadodariya K.; Vatedka R.; Tadepalli S.P.; Sarwade A.; Tyagi A.; Sharan V. (My University, 2025)
The distribution of Mg, Al, Si, Ca and Fe on the lunar surface are important to understand the petrological characteristics of the Moon and its geological evolution. We derived new elemental distribution maps using the Chandrayaan-2 Large Area Soft X-ray Spectrometer (CLASS) experiment onboard the Chandrayaan-2 Orbiter. These are the first set of maps derived from three years of CLASS data (2019–2022) at a spatial resolution of 150 km × 12.5 km. These maps are free of the topographic shadow effects and space weathering effects because the elemental abundances are derived only using X-ray spectra in the 0.5 to 20 keV energy range. CLASS derived abundances are compared to the elemental maps obtained using the Lunar Prospector Gamma Ray Spectrometer, with abundances of the lunar soil samples, and with XRF measurements of Chandrayaan-1 mission to establish its credibility. These maps derived using X-ray fluorescence spectroscopy are a new resource for lunar geochemical studies based on the most direct detection technique. © 2023 Elsevier Inc.